Dampak Penerapan Teknologi Terhadap Tingkat Stress Pegawai Lintas Generasi - Reyski Auryn; Yoke Pribadi Kornarius; Angela Caroline; Agus Gunawan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
Technostress is a stress that results from using the technology. Organizations must understand and control technostress because this stress has the potential to hinder employee innovative work behavior. Especially now that many organizations are filled with generation Y employees who are more fluent in using technology than generation X. This research was conducted on 101 employee respondents in business organizations consist of both generations. To investigate the affect of Technostress on Innovative Work Behavior, the data tested using regression, and then processed using a frequency distribution table to find differences in responses between generations. It appears that there was no impact of technostress on Innovative Work Behavior. However, there are differences in responses between generations for the techno-complexity dimension in the technostress variable.